C‐Abl tyrosine kinase plays a critical role in β2 integrin‐dependent neutrophil migration by regulating Vav1 activity. Issue 4 (1st April 2013) - Tong, Haibin; Zhao, Bin; Shi, Huifang; Ba, Xueqing; Wang, Xiaoguang; Jiang, Yong; Zeng, Xianlu
Abstract : A central regulatory role of c‐Abl kinase in controlling actin polymerization and membrane protrusion dynamics at leading edge, during β2 integrin‐dependent neutrophil migration. Abstract : The recruitment and migration of neutrophils are critical for innate immunity and acute inflammatory responses. However, the mechanism that regulates the recruitment and migration of neutrophils has not been well characterized. We here reveal a novel function of c‐Abl kinase in regulating neutrophil migration. Our results demonstrate that c‐Abl kinase is required for neutrophil recruitment in vivo and migration in vitro, and the inhibition of c‐Abl kinase activity has a significant impact on neutrophil migratory behavior. Moreover, c‐Abl kinase activation depends on β2 integrin engagement, and the activated c‐Abl kinase further regulates actin polymerization and membrane protrusion dynamics at the extended leading edges during neutrophil migration. In addition, we identify the Rho GEF Vav1 as a major downstream effector of c‐Abl kinase. The C‐terminal SH3‐SH2‐SH3 domain and proline‐rich region of Vav1 are required for its interaction with c‐Abl kinase, and c‐Abl kinase probably regulates the activity of Vav1 by direct phosphorylation at Tyr‐267 in the DH domain. Together, these results indicate that c‐Abl kinase plays a critical role in β2 integrin‐dependent neutrophil migration by regulating Vav1 activity.